Public libraries and their uses - Mudge, Mary (My University, 1905)
Introduction: The public library, as all other social institutions, has undergone many changes in its growth. At first these libraries were formed for the purpose of preserving books and docurnents, rather than as a means of providing reading for the public. It is impossible to state when the first collection was made, but indications of such collections are found in the inscription bricks and tablets buried in Egypt, which scholars today have agreed, belonged to a period as far back as the year 2000 B.C. It would seem that the history of public libraries would date from the first forms of writing, as people have saved their books since they have had any to save. Perhaps the earliest recorded collection of books is the one of an Egyptian king, Ramses 1,1400 B.C., which bore the inscription, "Dispensary of the Soul", showing how early the library came to be recognized as a force in civilization. Many of these early collections were of clay, baked brick, and later the papyrus and parchments. Some of them were very well regulated; the books catalogued and arranged systematically on the shelves, many of them being chained. Scattered records of different libraries are found from now on, in Africa, and Asia, these countries, rather than Europe, taking the lead. Perhaps one of the most noted of the early libraries is the Alexandrian library, which was destroyed shout A.D. 640. There is much dispute over the library the number of volumes varying from seven to one hundred thousand, but it would seem more probable to suppose that it contained even less than seven thousand, unless each chapter, as was sometimes the custom, was considered as a volume. The monasteries have been of the greatest aid in tracing back the history of libraries, as it was there that the collections were kept during the periods of revolutions, until the revival of learning when they were preserved at all. These copies were often very imperfect and poorly written, but they serve as the connecting link through this period. The order of the Benedictines was the leader in the revival of learning and very valuable libraries have been established through their efforts.
Citation: Mudge, Mary. Public libraries and their uses. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Influence of the Library; Means of Recreation; Means of Eduction; Theses